Implementasi Kecerdasan Buatan dalam Manajemen Proyek Agile dalam Mengatasi Tantangan dan Memaksimalkan Dampak - Lumbanraja, Harry Leonardo; Raharjo, Teguh; Fitriani, Anita Nur (AI Society & STMIK Indonesia, 2024)
The Agile methodology, with an 80% adoption rate, often faces challenges leading to project failures. This study investigates using artificial intelligence (AI) to overcome these challenges through a systematic literature review of 44 papers. It examines AI's impact on key Agile phases: envision, speculate, explore, adapt, and close. Findings highlight AI's critical role in improving project outcomes by addressing implementation challenges. AI tools aid in risk assessment and project selection during planning, enhance effort estimation and task allocation in speculation, improve team communication and technical issue resolution in exploration, optimize systems in adaptation, and provide valuable insights in closure. The paper offers guidance on effective AI integration to enhance Agile Project Management success.